Application of Innovative Projects in Information Systems - Okhunov, Mamatjon; Minamatov, Yusupali (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the use of innovative projects in information systems. On the one hand, this plays a crucial role in the production of the final product, while at the same time it contributes greatly to production costs and past development time. Thus, it is beneficial to use innovative projects that balance performance, costs and risks.